Enhanced phosphorus electrosorption using Fe, N-co-doped porous electrode via capacitive deionization - Chen, Xing (Environmental technology, 2024)
Excessive phosphorus discharge causes water eutrophication and disturbs the homeostasis of aquatic ecosystems. Capacitive deionization (CDI) has been proven to be a more energy-efficient and environmentally friendly technology for removing phosphorus. Raw carbon (Raw C) electrodes are widely used in CDI. However, the phosphorus removal capacity of most unmodified Raw C still needs to be enhanced. Therefore, the Fe, N-co-doped carbon prepared in this study was expected to further improve the phosphorus removal performance. Herein, the optimal electrode with 5% Fe (FeNC) had an approximately 2.7 times higher adsorption capacity than Raw C. At a low concentration (5 mg P/L), FeNC exhibited a high maximum removal capacity of 4.28 mg P/g. Under reversed voltage, the phosphorus was easily desorbed by deionized water. Ion competition studies showed that coexisting ions adversely affected phosphorus adsorption onto FeNC in the order SO42- > NO3- > Cl-. Furthermore, the energy consumption of FeNC was calculated to be as low as 0.0069 kWh/g P and 0.023 kWh/m3 water under 1.2 V. More importantly, phosphorus removal by FeNC during CDI was demonstrated in simulated natural water from the Jinjiang River (Chengdu, China). This study indicated that FeNC is expected to be a potential electrode for CDI dephosphorization